Status Preferences and Economic Growth - Richard B. Howarth; Kjell Arne Brekke (Statistics Norway, Research Department, 1998)
This paper examines the implications of status-seeking behavior for long-term growth in a competitive economy. We explore the intuitive hypothesis that the quest for enhanced economic status leads to excessive levels of production and consumption. In a Ramsey growth model in which preferences are altered to include a concern for relative consumption, status seeking has no impacts on the economys long-run equilibrium in the absence of a labor-leisure tradeoff. Relative consumption effects do, however, induce short-term departures from efficient resource allocation, either augmenting or depressing consumption growth rates in accordance with the elasticity of substitution between consumption and status. In the case where social status is defined in terms of the relative accumulation of manufactured capital, status seeking leads to excessive rates of short-run growth and inefficiently high levels of capital and consumption in the long-run equilibrium. Similar results hold when preferences embody a concern for career status as captured by the relative accumulation of human capital, and when relative consumption effects are accompanied by a labor-leisure tradeoff.
Keywords: O40; 330; Growth; Status preferences; relative consumption; relative capital